Approach to Mental Retardation and Global Developmental Delay - ASHRAFI, Mahmoud Reza (Iranian Journal of Child Neurology, 2011)
Objective Mental Retardation (MR) or Intellectual Disability is one of three chronic and disabling neurological disorders of children and adolescents. Its prevalence is estimated 1-3% of the population. MR is defined as significant sub-average intellectual functioning and adaptive behavior that become detectable before the age of 18. MR may come into view before 5 years as delay in at least two developmental domains which is called Global Developmental Delay (GDD). The causes of mental retardation can be considered under the titles of prenatal, perinatal and postnatal factors. Prenatal causes account for approximately 60 -80 % of the etiological factors. All patients with GDD / MR should undergo a stepwise diagnostic approach, because a specific diagnosis leads to opportunity for treatment, future planning and genetic counseling. History, physical examination and neurodevelopmental examinations are the most important parts of the approach. Recent advances in cytogenetic investigations and neuroimaging studies have led to recognition of new disorders and improvement of the diagnostic yield. Keywords: Mental retardation ; global developmental delay; diagnostic yield.